Effect of Eco-Friendly Wind Turbine Teaching Aids on Elementary Students’ Energy Conceptual Understanding - Aisyah Rahmah Ummi Kurnilasari; Risalul Ummah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study examines the effect of environmentally friendly science teaching aids in the form of a windmill integrated into experimental learning on third-grade students’ conceptual understanding of energy in Madrasah Ibtidaiyah. A quantitative quasi-experimental method with a nonequivalent control group design was employed. The sample consisted of 46 students selected through purposive sampling, including 24 in the experimental group and 22 in the control group. The experimental group received experimental learning supported by windmill-based teaching aids made from recycled materials, while the control group received experimental learning without teaching aids. Data were collected using a validated multiple-choice test measuring conceptual understanding across cognitive levels C1–C4. The instrument demonstrated acceptable reliability (Cronbach’s α ≥ 0.70). Data analysis included descriptive statistics, Shapiro–Wilk normality test, Levene’s homogeneity test, independent samples t-test, and N-Gain analysis. The results showed no significant difference in pretest scores, indicating equivalent baseline understanding. However, posttest results revealed a significant difference favoring the experimental group. The normalized gain was higher in the experimental group (59.21%, moderate–high) compared to the control group (11.22%, low). The effect size was very large (Cohen’s d = 3.47), indicating a strong practical impact. These findings demonstrate that integrating environmentally friendly windmill-based teaching aids into experimental learning significantly improves students’ conceptual understanding of energy.